The Influence of Service Quality, Price Perceptions and Taste on Consumer Satisfaction of Mie Gacoan Among Purwokerto Students - Amalia, Nabila Ayu; Hidayah, Arini; Widhiandono, Hengky; Alfalisyado, Alfalisyado (Jurnal Ekonomi, 2024)
This study examines the complex relationships that influence the satisfaction of Purwokerto students who are consumers of Mie Gacoan. Within the framework of correlation studies, this research plays a crucial role in revealing the complex and comprehensive interactions between various variables in the field. By using a quantitative approach, this research identifies the nature and extent of the relationship between two or more variables. The main findings of this research include: 1) Service quality has an influence on consumer satisfaction. 2) Price perceptions have an impact on consumer satisfaction. 3) Taste influences consumer satisfaction.